(untitled) (Proceedings of International Educators Conference, 2024)
Terms related to pedagogy, which have become (in some sense) a separate field of linguistics, have been formed and are actively developing. Currently, it is difficult to calculate the bibliography of terms related to pedagogy. A lot of work has been done on various aspects of linguistic terminology, but at the same time, we can note that the material of terms related to pedagogy in linguistics is rare. The main goal of our thesis is to reveal the pragmatic features of pedagogical termininguistics and to highlight their differences in English and Karakalpak languages.